Expert Answers

An illustration of the letter 'A' in a speech bubbles

Given the equation:

`ln(2x-1) = 4`

`` First we will rewrite into the exponent form.

" if `ln a = b ==gt a = e^b`  "

`==gt (2x-1)= e^4`

`` Now we will solve for x.

`==gt 2x = e^4 +1`

`` `==gt x = (e^4+1)/2 ~~ 27.8`




To solve this question, we need to remember a certain fact about functions:

`f^-1(f(x)) = x`

This relation means that when we take the inverse of a function, we simply get our original input back out.

This relation is especially relevant for us because (as you can see...

(The entire section contains 2 answers and 270 words.)

Unlock This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Start your 48-Hour Free Trial
Approved by eNotes Editorial Team